2018
DOI: 10.4300/jgme-d-17-00465.1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Comprehensive Medical Knowledge Curriculum in Internal Medicine Using Team-Based Learning

Abstract: Implementing a comprehensive medical knowledge curriculum using TBL in an internal medicine residency was feasible, and resulted in high faculty acceptance and learner satisfaction. Departmental support of a TBL champion, flexible faculty development, and well-designed resource materials were determinants of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…On the other hand, the use of digital presentation slides may shift the conference away from an interactive flipped classroom which is more effective than a lecture-based format. [20][21][22][23][24] Although speculative, we also believe that the emphasis on rare and lifethreatening presentations likely has an effect on learners' diagnostic reasoning and may distort their assessment of relative probabilities when constructing differential diagnoses outside of morning report as it may lead them to biased towards these rare conditions.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the use of digital presentation slides may shift the conference away from an interactive flipped classroom which is more effective than a lecture-based format. [20][21][22][23][24] Although speculative, we also believe that the emphasis on rare and lifethreatening presentations likely has an effect on learners' diagnostic reasoning and may distort their assessment of relative probabilities when constructing differential diagnoses outside of morning report as it may lead them to biased towards these rare conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Group work was another preference identified by some participants. A study of team-based learning (TBL) feasibility in an internal medicine residency program showed that the residents thought they learned more medical knowledge through this approach than through lectures [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, we described the planning, design, faculty development, lesson structure, satisfaction with, and feasibility of this curriculum. 11 We hypothesized that an active learning approach using TBL would result in more effective knowledge acquisition than lectures and lead to improvements on residents' Internal Medicine In-Training Examination (IM-ITE) scores. We now report on IM-ITE performance of 2 groups of residents, one exposed to a lecture curriculum and one to a TBL curriculum.…”
Section: Introductionmentioning
confidence: 99%